Clinical epidemiology of amyotrophic lateral sclerosis in Liguria, Italy: An update of LIGALS register. Issue 7 (16th November 2016) - Scialò, Carlo; Novi, Giovanni; Bandettini di Poggio, Monica; Canosa, Antonio; Sormani, Maria Pia; Mandich, Paola; Origone, Paola; Truffelli, Romina; Mancardi, Giovanni Luigi; Caponnetto, Claudia
Abstract: Our objectives were: (1) to assess amyotrophic lateral sclerosis (ALS) incidence and its trend over time in Liguria, an Italian north-western region, performing an analysis of data prospectively collected from 1 January 2009 to 31 December 2014; (2) to determine the mean and median survival in the 2009–2014 Ligurian ALS incident cases; and (3) to evaluate the presence of disease prognostic factors. The Liguria Register for ALS (LIGALS) is an ongoing, multicentre prospective register enrolling all ALS incident cases in Liguria. Cases were identified using several concurrent sources. ALS diagnosis was based on El Escorial revised criteria (EEC-R). Two hundred and ninety-eight patients were enrolled in this study. The mean annual crude incidence rate in the 2009–2014 period was 3.11/100, 000 population (95% CI 2.77–3.49); the point prevalence at 31 December 2014 was 7.85/100, 000 (95% CI 6.54–9.36) population. Survival analysis demonstrated a median survival from symptom onset of 37.0 months (95% CI 32.0–42.0). In conclusion, ALS crude incidence in Liguria is higher compared to other Italian regions. Clinical and epidemiological data are comparable with those of the Italian ALS population. Survival analysis showed that higher age at onset, bulbar onset, definite EEC-R diagnostic category and a shorter diagnostic delay are related with worse outcomes.